Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's analyze the given function and the expressions step-by-step to determine which expression is equivalent to [tex]\((k + k)(4)\)[/tex]:
1. Understand the function [tex]\(k(x)\)[/tex]:
Given:
[tex]\[ k(x) = 5x - 6 \][/tex]
2. Evaluate the function [tex]\(k(x)\)[/tex] at [tex]\(x = 4\)[/tex]:
[tex]\[ k(4) = 5(4) - 6 = 20 - 6 = 14 \][/tex]
3. Understand what [tex]\((k + k)(4)\)[/tex] means:
[tex]\((k + k)(4)\)[/tex] is equivalent to:
[tex]\[ k(4) + k(4) \][/tex]
Since we already found that [tex]\(k(4) = 14\)[/tex], we have:
[tex]\[ k(4) + k(4) = 14 + 14 = 28 \][/tex]
4. Now let's analyze each provided expression to see which one evaluates to 28:
- Expression 1: [tex]\(5(4 + 4) - 6\)[/tex]
[tex]\[ 5(4 + 4) - 6 = 5(8) - 6 = 40 - 6 = 34 \][/tex]
This evaluates to 34, not 28.
- Expression 2: [tex]\(5(5(4) - 6) - 6\)[/tex]
[tex]\[ 5(5(4) - 6) - 6 = 5(20 - 6) - 6 = 5(14) - 6 = 70 - 6 = 64 \][/tex]
This evaluates to 64, not 28.
- Expression 3: [tex]\(54 - 6 + 54 - 6\)[/tex]
[tex]\[ 54 - 6 + 54 - 6 = 48 + 48 = 96 \][/tex]
This evaluates to 96, not 28.
- Expression 4: [tex]\(5(4) - 6 + 5(4) - 6\)[/tex]
[tex]\[ 5(4) - 6 + 5(4) - 6 = 20 - 6 + 20 - 6 = 14 + 14 = 28 \][/tex]
This evaluates to 28, which matches our computed value for [tex]\((k + k)(4)\)[/tex].
Therefore, the expression that is equivalent to [tex]\((k + k)(4)\)[/tex] is:
[tex]\[ 5(4) - 6 + 5(4) - 6 \][/tex]
1. Understand the function [tex]\(k(x)\)[/tex]:
Given:
[tex]\[ k(x) = 5x - 6 \][/tex]
2. Evaluate the function [tex]\(k(x)\)[/tex] at [tex]\(x = 4\)[/tex]:
[tex]\[ k(4) = 5(4) - 6 = 20 - 6 = 14 \][/tex]
3. Understand what [tex]\((k + k)(4)\)[/tex] means:
[tex]\((k + k)(4)\)[/tex] is equivalent to:
[tex]\[ k(4) + k(4) \][/tex]
Since we already found that [tex]\(k(4) = 14\)[/tex], we have:
[tex]\[ k(4) + k(4) = 14 + 14 = 28 \][/tex]
4. Now let's analyze each provided expression to see which one evaluates to 28:
- Expression 1: [tex]\(5(4 + 4) - 6\)[/tex]
[tex]\[ 5(4 + 4) - 6 = 5(8) - 6 = 40 - 6 = 34 \][/tex]
This evaluates to 34, not 28.
- Expression 2: [tex]\(5(5(4) - 6) - 6\)[/tex]
[tex]\[ 5(5(4) - 6) - 6 = 5(20 - 6) - 6 = 5(14) - 6 = 70 - 6 = 64 \][/tex]
This evaluates to 64, not 28.
- Expression 3: [tex]\(54 - 6 + 54 - 6\)[/tex]
[tex]\[ 54 - 6 + 54 - 6 = 48 + 48 = 96 \][/tex]
This evaluates to 96, not 28.
- Expression 4: [tex]\(5(4) - 6 + 5(4) - 6\)[/tex]
[tex]\[ 5(4) - 6 + 5(4) - 6 = 20 - 6 + 20 - 6 = 14 + 14 = 28 \][/tex]
This evaluates to 28, which matches our computed value for [tex]\((k + k)(4)\)[/tex].
Therefore, the expression that is equivalent to [tex]\((k + k)(4)\)[/tex] is:
[tex]\[ 5(4) - 6 + 5(4) - 6 \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.